microRNA-184 distribution and consequences on glial septate junctions and the blood-brain barrier - Sravya Paluri; Vanessa J. Auld (PLoS ONE, 2025)
Cellular permeability barriers restrict the diffusion of solutes, pathogens, and cells across tissues. In Drosophila melanogaster , septate and tricellular junctions create permeability barriers in epithelia and the blood-brain barrier in glia. In vitro , and in vivo studies in the epithelia of the Drosophila wing imaginal discs identified microRNA-184 (miR-184) as a potential regulator of a subset of pleated septate and tricellular junction proteins. However, which tissues express miR-184, and the consequences of miR-184 expression on the blood-brain barrier has not been examined. Using a miR-184 sensor, we found that miR-184 is absent in tissues with pleated septate junctions but is present in tissues with smooth septate junctions. When expressed in the subperineurial glia that form the blood-brain barrier, miR-184 resulted in the loss of targeted septate junction proteins, a compromised blood-brain barrier, decreased locomotion, and lethality. Interestingly, qRT-PCR analysis revealed that miR-184 expression did not alter mRNA levels of targeted genes. Conversely, expression of miR-184 led to an increase in the mRNA and expression of the non-target Nervana2 protein. Thus, mRNA-184 can regulate multiple pleated septate junction proteins either directly through loss of translation or indirectly by disruption of the septate junction domain.